1990
DOI: 10.1037/0882-7974.5.1.101
|View full text |Cite
|
Sign up to set email alerts
|

Depressive symptom patterns among older women.

Abstract: The structure of depressive symptom patterns was investigated in a community sample of 344 women between the ages of 51 and 92 who were administered the SCL-90-R Depression and Additional Symptoms Scales. Confirmatory factor analysis was used to test alternative measurement hypotheses implied by clinical formulations of depressive symptom patterns among elderly persons. The findings show support for the hypothesis that 2 somewhat different depressive syndromes, along with 4 more delimited forms of distress, un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
21
0
2

Year Published

1997
1997
2008
2008

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 36 publications
3
21
0
2
Order By: Relevance
“…This is a dilemma because traditionally women have not been encouraged to develop traits that improve with age, such as wisdom and intellectual competence (Stoddard, 1983), but have learned that physical beauty is the quality which affords them the most power and esteem in our culture. Perhaps media images of aging women help to explain why therapists have recently found a "depletion syndrome" prevalent in older women, characterized by feelings of worthlessness, no interest in things, a sense of hopelessness, and thoughts of death (Newmann, Engel, & Jensen, 1990). Because representation in the media signifies social existence, and underrepresentation signifies inexistence (Gerbner as cited in Tuchman, 1979), the media's failure to portray aging female characters reinforces an unattainable cultural standard that perpetuates women's struggle to fight aging at all cost.…”
Section: Discussionmentioning
confidence: 99%
“…This is a dilemma because traditionally women have not been encouraged to develop traits that improve with age, such as wisdom and intellectual competence (Stoddard, 1983), but have learned that physical beauty is the quality which affords them the most power and esteem in our culture. Perhaps media images of aging women help to explain why therapists have recently found a "depletion syndrome" prevalent in older women, characterized by feelings of worthlessness, no interest in things, a sense of hopelessness, and thoughts of death (Newmann, Engel, & Jensen, 1990). Because representation in the media signifies social existence, and underrepresentation signifies inexistence (Gerbner as cited in Tuchman, 1979), the media's failure to portray aging female characters reinforces an unattainable cultural standard that perpetuates women's struggle to fight aging at all cost.…”
Section: Discussionmentioning
confidence: 99%
“…Alguns 19,20,21,22 , isso porque a normatização das escalas produz um escore único, fruto do somatório dos itens da escala, dentre os quais se encontram aqueles relacionados ao aspecto somático da depressão como os distúrbios do sono e do apetite, perda de peso, fadiga, perda da libido, dentre outros.…”
Section: Elaboração E Validação Da Escala De Depressão Para Idososunclassified
“…De um modo geral, as escalas de depressão são eficazes na avaliação do nível de depressão de pessoas adultas; contudo, para indivíduos idosos, os níveis detectados podem não ser fidedignos, uma vez que os itens relacionados aos sintomas somáticos, nesse caso, servem tanto para diagnosticar sintomas de depressão como para diagnosticar sintomas naturais decorrentes do próprio envelhecimento 20,21,22 . Além disso, doenças comuns na terceira idade podem superestimar o diagnóstico de depressão em idosos, ao mesmo tempo em que o uso de medicamentos pode mascarar sintomas 23 18 definem, ainda, que pacientes idosos tendem a obter baixos escores nos sintomas cognitivos da depressão e altos escores nos sintomas somáticos da mesma.…”
Section: Elaboração E Validação Da Escala De Depressão Para Idososunclassified
“…In addition, older Australian women are more vulnerable to musculoskeletal disorders (Australian Bureau of Statistics, 1982), and, as Verbrugge (1990) has pointed out, as women age, they are more likely to suffer from chronic conditions such as anaemia, bladder infections, spinal degeneration and deformity, varicose veins, colitis, and migraine headaches. In terms of psychological problems, Newmann, Engel, and Jensen (1990) found that, compared to younger women, those aged over 51 were more likely to exhibit depression and associated symptoms such as disturbances of sleep; lack of energy; feelings of loneliness and worthlessness; lack of interest in life; loss of appetite; sense of hopelessness; thoughts of death, dying, and suicide; and feelings of guilt and shame.…”
mentioning
confidence: 99%